1. 4 (x+2)=28
Simplifying
4(x + 2) = 28
Reorder the terms:
4(2 + x) = 28
(2 * 4 + x * 4) = 28
(8 + 4x) = 28
Solving
8 + 4x = 28
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-8' to each side of the equation.
8 + -8 + 4x = 28 + -8
Combine like terms: 8 + -8 = 0
0 + 4x = 28 + -8
4x = 28 + -8
Combine like terms: 28 + -8 = 20
4x = 20
Divide each side by '4'.
x = 5
Simplifying
x = 5
2. 2 (x+4)=28
Simplifying
2(x + 4) = 28
Reorder the terms:
2(4 + x) = 28
(4 * 2 + x * 2) = 28
(8 + 2x) = 28
Solving
8 + 2x = 28
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-8' to each side of the equation.
8 + -8 + 2x = 28 + -8
Combine like terms: 8 + -8 = 0
0 + 2x = 28 + -8
2x = 28 + -8
Combine like terms: 28 + -8 = 20
2x = 20
Divide each side by '2'.
x = 10
Simplifying
x = 10